Stereotypical Portrayal of Indian and French in Richard C. Morais’ The Hundred-Foot Journey (2010): An Orientalism Study - Rhena Indria Haryono (Passage, 2019)
Globalization has made understanding of cultural diversity more important. However, one challenge caused by cultural diversity is the existence of cultural stereotypes since stereotyping can lead to prejudice and discrimination. This study attempts to examine the stereotypical portrayals of the Indians and the French in Morais’ The Hundred-Foot Journey (2010) from Orientalism perspective since studies on this work are still limited. This study draws on Said’s (1978) theory on Orientalism. In addition, this study also employs Little’s (1966) theory on characterization to support the analysis of the data. The finding reveals the author presents Indian and French in a contrast way in which one is regarded as inferior and the other as superior. Furthermore, it is also found that the relation between them is similar to the relations between the Orient and the Occident which are argued by Said (1978) as a kind of relationship which distinguishes ‘self’ and ‘other’ that is filled with power and domination. Keywords: Orientalism, stereotypes, othering, power